Assessing fatty acid biostatus: Red blood cells or plasma?. Issue 8 (2nd August 2013) - Harris, William S.
Abstract Omega‐3 fatty acid (n‐3 FA) biostatus can be estimated using red blood cell (RBC) membranes or plasma. The sample type that exhibits the lower within‐person variability and is less affected by an acute dose of n‐3 FA is preferred in clinical practice. The experiments described here indicate that RBC‐based metrics are superior to plasma‐based for use in patient care.